Reuse in implementations of middleware for digital TV - Teixeira, César A. C.; Sardinha, Eduardo D. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
This paper presents an approach to develop new instances of interactive digital TV -- DTV middleware based on reuse and port of existing implementations of these middlewares for other hardware platforms. Design characteristics of DTV middleware and software portability concepts are used to propose a reuse model. A proof of concept using an implementation of the Brazilian DTV middleware (Ginga) showed that the approach can be useful within specific portability contexts.